Analisis Dempster Shafer Dalam Mendiagnosa Penyakit Coffea Canephora (Kopi Robusta) - Khairu Fahriz Ramadhan; Afif Badawi (Journal of Information System Research (JOSH), 2023)
Indonesia is one of the world's largest coffee producers and has a reputation for producing high quality coffee. As a country located in the tropics with fertile soil, climate, and suitable topography, Indonesia has ideal conditions for growing coffee. Various varieties of coffee in Indonesia, including Arabica and Robusta, grow well in various regions such as Java, Sumatra, Sulawesi, Bali, Nusa Tenggara, Papua and Kalimantan. Some of the typical Indonesian coffee varieties include Gayo Coffee from Aceh, Mandailing Coffee from North Sumatra, Toraja Coffee from South Sulawesi, and Bali Coffee from Bali. Coffee plants can be attacked by various diseases, which can affect growth, quality and yield. The Dempster-Shafer analysis approach for diagnosing disease in Robusta coffee plants is based on the theory of trust (evidence theory) and provides a strong framework for modeling uncertainty in disease diagnosis. The first step is to collect observational data on various disease indicators such as leaf discoloration, decay symptoms, and stunted growth. By calculating the degree of confidence and uncertainty, we can produce reliable conclusions about the presence of disease in Robusta coffee plants. In addition, we also developed the Dempster-Shafer model to identify the stage or severity of the disease, which can assist farmers in taking appropriate action. The results show that the Dempster-Shafer analysis approach provides accurate and reliable results in diagnosing Robusta coffee disease. This model can also provide valuable information in identifying disease stages, which can support effective disease management and control.